Geometrical and Optical Properties of Optical Components Manufactured by Means of Stereolithography - Bartels, Dominic; Heise, Miriam; Schmidt, Michael (Optics, 2024)
Additive manufacturing (AM) is a fast-growing technology that supports the rapid fabrication of prototypes. Already, employing AM technologies in early product development stages can help to accelerate the time from conceptualisation phase to the market entry. Furthermore, advances in the field of materials, such as highly transparent resins in the visible wavelength spectrum, also open application potentials for the design and fabrication of optical components. Three highly transparent resins from different suppliers are studied in this work regarding their influence on the geometrical and optical properties of additively manufactured components. The different materials were processed using a masked stereolithography 3D printer. Geometrical and optical properties of the generated test samples were analysed by means of laser scanning microscopy and spectrophotometry, respectively. A clear correlation between optical properties of the resin and the solidified samples was identified. It was further found that while spin coating does not significantly affect the geometrical properties, a strong influence on the resulting optical properties could be observed. The highest transmission properties, in the range of up to 90%, were determined for samples that were spin-coated on both surfaces. Thus, applying a spin coating operation to additively manufactured optical components is recommended for the highest transmission propertie
Keywords: stereolithography; mSLA; optical components; transmission properties; 3D printing